Education transformation in Malaysia through spiritual intelligence: Perspective of Imam Al Ghazzali - Hanefar, S.B.; Siraj, Saedah; Sa’ari, C.Z. (2014)
Education in Malaysia is going through a transformation period from knowledge based education to value based (holistic) education which is being clearly objectified in the National Education Philosophy. But somehow rather the implementation of this holistic education seems to be vague across many stages of education in Malaysia especially the implementation of spiritual intelligence. There is a gap between the current practices in our education industry with the National Education Philosophy. Many social problems among students and adolescents are being reported that are very alarming and could be the hindrance factor for Malaysia to achieve its Vision 2020. To achieve human excellence as the vicegerent of God (khalifah of Allah), it is very crucial for human beings to balance his/her duniawi and ukhrawi. The aim of this research is to provide a platform in transforming Malaysian education system through spiritual intelligence. The spiritual intelligence components were derived from the content analysis done on Al Ghazzali’s Ihya Ulumuddin (Book 3).